2015
DOI: 10.1007/s10956-015-9558-4
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Inquiry Self-Efficacy and Computer Game Self-Efficacy as Predictors and Outcomes of Middle School Boys’ and Girls’ Performance in a Science Assessment in a Virtual Environment

Abstract: The primary aim of the study was to examine whether performance on a science assessment in an immersive virtual environment was associated with changes in scientific inquiry self-efficacy. A secondary aim of the study was to examine whether performance on the science assessment was equitable for students with different levels of computer game self-efficacy, including whether gender differences were observed. We examined 407 middle school students' scientific inquiry self-efficacy and computer game self-efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 39 publications
0
14
0
3
Order By: Relevance
“…Sixth graders increased significantly in science self-efficacy after exposure to a problem-based multimedia program about the solar system (Liu et al 2006). Experience of virtual worlds also significantly influenced middle school students' beliefs in their ability to do scientific inquiry (Bergey et al 2015;Chen et al 2014).…”
Section: Sources Of Self-efficacymentioning
confidence: 99%
“…Sixth graders increased significantly in science self-efficacy after exposure to a problem-based multimedia program about the solar system (Liu et al 2006). Experience of virtual worlds also significantly influenced middle school students' beliefs in their ability to do scientific inquiry (Bergey et al 2015;Chen et al 2014).…”
Section: Sources Of Self-efficacymentioning
confidence: 99%
“…Self‐efficacy affects the choice of activities, the level of effort spent, resistance, and performance in coping with difficulties in order to solve a problem and to accomplish a task (Bandura, ). It is widely accepted that self‐efficacy is related to general academic learning achievements and performance of learning specific skills (Bergey, Ketelhut, Liang, Natarajan, & Karakus, ; Girasoli & Hannafin, ). On the other hand, strong relationships between self‐efficacy and digital learning/programming have also been extensively studied (Chiu & Tsai, ; Davidsson et al, ; Komarraju & Nadler, ; Ramalingam, LaBelle, & Wiedenbeck, ; Richardson, Abraham, & Bond, ; Tsai, Chuang, Liang, & Tsai, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research comparing the academic achievement of males and females using V-Labs have indicated inconsistent results. Some have revealed that both males and females have similar achievement (Bergey, et al, 2015) while some have revealed that males perform better (Gambari et al, 2017). However, it is worth mentioning that none of these studies have looked at gender differences using two different approaches (inquiry-based V-Labs and IBL alone).…”
Section: Discussionmentioning
confidence: 99%